Electrically Triggered Drug Delivery from Novel Electrospun Poly(Lactic Acid)/Graphene Oxide/Quercetin Fibrous Scaffolds for Wound Dressing Applications - Alexa-Maria Croitoru; Yasin Karaçelebi; Elif Saatcioglu; Eray Altan; Songul Ulag; Huseyin Kıvanc Aydoğan; Ali Sahin; Ludmila Motelica; Ovidiu Oprea; Bianca-Maria Tihauan; Roxana-Cristina Popescu; Diana Savu; et al. (MDPI AG, 2021)
The novel controlled and localized delivery of drug molecules to target tissues using an external electric stimulus makes electro-responsive drug delivery systems both feasible and desirable, as well as entailing a reduction in the side effects. Novel micro-scaffold matrices were designed based on poly(lactic acid) (PLA) and graphene oxide (GO) via electrospinning. Quercetin (Q), a natural flavonoid, was loaded into the fiber matrices in order to investigate the potential as a model drug for wound dressing applications. The physico-chemical properties, electrical triggering capacity, antimicrobial assay and biocompatibility were also investigated. The newly fabricated PLA/GO/Q scaffolds showed uniform and smooth surface morphologies, without any beads, and with diameters ranging from 1107 nm (10%PLA/0.1GO/Q) to 1243 nm (10%PLA). The in vitro release tests of Q from the scaffolds showed that Q can be released much faster (up to 8640 times) when an appropriate electric field is applied compared to traditional drug-release approaches. For instance, 10 s of electric stimulation is enough to ensure the full delivery of the loaded Q from the 10%PLA/1%GO/Q microfiber scaffold at both 10 Hz and at 50 Hz. The antimicrobial tests showed the inhibition of bacterial film growth. Certainly, these materials could be loaded with more potent agents for anti-cancer, anti-infection, and anti-osteoporotic therapies. The L929 fibroblast cells cultured on these scaffolds were distributed homogeneously on the scaffolds, and the highest viability value of 82.3% was obtained for the 10%PLA/0.5%GO/Q microfiber scaffold. Moreover, the addition of Q in the PLA/GO matrix stimulated the production of IL-6 at 24 h, which could be linked to an acute inflammatory response in the exposed fibroblast cells, as a potential effect of wound healing. As a general conclusion, these results demonstrate the possibility of developing graphene oxide-based supports for the electrically triggered delivery of biological active agents, with the delivery rate being externally controlled in order to ensure personalized release.